Circumaortic Left Renal Vein and Double Right Renal Vein: A Case Report - Naveen K.,; Ravindra S.,; Satheesha NB.,; Mohandas Rao KG.,; Ashwini AP.,; Jyothsna P., (Department of Surgery, UKM Medical Centre, 2015)
Venous malformation of the kidney is not uncommon. However, bilateral variation of renal veins is of rare occurrence and is clinically significant. In the present case, left renal vein divided into left pre and retro-aortic renal veins which passed in front and behind the abdominal aorta respectively, together forming a circumaortic renal vein. The retro-aortic limb received left testicular vein at a distance of 5.8 cm from inferior vena cava and pre-aortic vein received left suprarenal vein at a distance of 4.2 cm from inferior vena cava. Pre-aortic and retro-aortic veins drained into IVC separately about 4 cm apart from each other. On the right side, two separate renal veins (superior and inferior) were present. Both of them drained into inferior vena cava separately and about 2.6 cm apart from each other. This aberrant pattern of renal vein may affect the venous drainage of kidney and testis leading to renal hypertension and varicocele. Such variations should be known to urologists and surgeons before commencing any surgical and interventional procedures.